Analisis Variasi Struktur Kalimat Pada Teks LaporanHasil Observasi Karangan Siswa Kelas Vii Di Smp Negeri 2Boyolali - MUDZAKIR, FITRONI; , Dra. Atiqa Sabardila, M. Hum (2016)
This study aims to (1) describe the extent of the error in using capital letters and punctuation in the writings result of eighth grade students at Muhammadiyah 4 Surakarta Junior High School, (2) describe the causes of errors capital letters and punctuation on the official letter written by eighth grade students at Muhammadiyah 4 Surakarta Junior High School. This study using descriptive qualitative method. Source of data originated from the writings result of the students in made official letter. This research collecting technique using observe and record technique and continued with documentation technique and in-dept interview. The teqniques of data analysis in this research is using the comparison method which determined by the high level of suitability, harmony, conformity, approptiateness, or the similarity with a determinants (writing) concerned as well as basic or standard. The validity of data used is using theoretical triangulation. The results of this study indicate a fault capitalization those found in (1) letterhead as many as 9,5%, (2) the date and the making of 3,2%, (3) number, attachments, and about as many as 4,7%, (4) the destination address by 8.6%, (5) opening, content and cover as many as 29,6%, (6) the name of the light by 2%. As for the errors found on the use of punctuation that is (1) error point mark found on the letterhead were 2,3%, the creation date of the letter of 2%, addressee 3,2%, opener, content, and cover 5,9%, the name of the light by 2%. (2) The use of a comma Errors found on the letterhead of 3,5% the creation date of the letter of 0.5%, addressee of 0.8%, opener, content, and cover 4,1%. (3) Errors use colons were found at the address of 1.1%, letter opener and 2.6%. (4) Any misuse hyphens are found on the date of a letter of 1,4%, opener, content, and cover as much as 2.6%. (5) Error apostrophe found in the cover letter opener and 5,9%. The factor of the error capitalization and punctuation in letter written by eight grade students at Muhammadiyah 4 Junior High School of Surakarta in spite of the factors that affect it. The first factor is the difficulty in writting official letter, second is the lack of mastery the rule of Indonesia language, and the third is the lack of fokus and meticulousness in writing. Keywords: Offical Letter, Capital Letter Mistakes and Errors Punctuation.